"Nanotraps" in porous electrospun fibers for effective removal of lead(ii) in water. Issue 7 (20th January 2016) - Senthamizhan, Anitha; Balusamy, Brabu; Celebioglu, Asli; Uyar, Tamer
Abstract : In this report, we demonstrated a synthetic strategy for the effective removal of Pb 2+ in water by creating stable "nanotraps" in electrospun porous cellulose acetate fibers encapsulated with dithiothreitol capped gold nanoclusters. Abstract : Here, we have put in conscientious effort to demonstrate the careful design of binding sites in fibers and their stability for enhanced adsorption of metal ions, which has proven to be a challenging task until now. Dithiothreitol capped gold nanoclusters (AuNCs) are successfully encapsulated into a cavity in the form of pores in electrospun porous cellulose acetate fibers (pCAFs) and their assembly creates a "nanotrap" for effective capture of Pb 2+ . The enhanced immobilization capacity of AuNCs into the interiors of the fibers and their non-aggregated nature offer enhanced adsorption sites, thus reaching maximum extraction capacity up to 1587 mg g −1 for Pb 2+ . The remarkable finding from this approach has shown that the diffusion of Pb 2+ into the interiors of the AuNC encapsulated porous cellulose acetate fiber (pCAF/AuNC) is in line with the penetration depth of AuNCs. The effectiveness of the pCAF/AuNC has been compared with that of the AuNC decorated non-porous cellulose acetate fibers (nCAF/AuNC). The findings have shown a remarkable improvement in the adsorption efficiency by increasing the availability and stability of adsorption sites in the pCAF/AuNC. We strongly believe that the proposed approach might provide a new insight into developing nanotraps to eliminate the usual limitations including denaturation of adsorbents on supported matrices.